Formation aux métiers de la petite enfance et analyse des pratiques - Souâd Denoux; Bernard Pueyo (Presses universitaires de la Méditerranée, 2012)
This contribution pursues the thought led during the symposium titled 'The training in the early childhood professions and the practices analysis'. After stating the different meanings of such an expression, we will question the link between the training and the practices analysis. We will bring out its shared features inside the early childhood professions trainings. It becomes apparent that including the practices analysis as a prime tool draws on the unification process of the field at the level of its professionalization. Finally, the status given to the practices analysis in the area of early childhood care prove to be useful as an indicator of its ability to come to terms with its renewing.